THE EFFECT OF WORKING CAPITAL TURNOVER AND SALES GROWTH ON PROFITABILITY IN CONSUMER NON-CYCLICALS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2020-2022 PERIOD - Nurfazilah; Amna Nabila; Fitri Andriani; Koko Bustami (Universitas Efarina, 2022)
The aim of this research is to find out the influence of working capital turnover and sales growth on profitability in non-cyclical consumer companies listed on the Indonesian Stock Exchange (IDX) for the 2020-2022 period. This research was conducted using a quantitative method approach in the form of numbers and analyzed using statistics. The scope of the research took non-cyclical consumer companies listed on the Indonesia Stock Exchange, totaling 125 companies and the sample used was 46 companies with a sampling technique using Purposive Sampling, namely only taking samples from parts that were directly related to the research. Analysis using multiple linear regression. The results of the partial hypothesis testing research showed that working capital turnover had no effect on profitability, the second result was that there was an influence of sales growth on profitability, and the results of the simultaneous test showed that working capital turnover and sales growth had a simultaneous influence on profitability in consumer companies. non-cyclical listed on the Indonesia Stock Exchange for the 2020-2023 period.